2019
DOI: 10.1093/cdn/nzz051.p04-160-19
|View full text |Cite
|
Sign up to set email alerts
|

Use of Policy, Systems, and Environmental Change Strategies Within Supplemental Nutrition Assistance Program Education (SNAP-Ed), 2014–2016 (P04-160-19)

Abstract: Objectives SNAP-Ed is the nutrition education and obesity prevention component of the Supplemental Nutrition Assistance Program, the nation's largest nutrition assistance program for eligible low-income households. The 2010 Child Nutrition Act directed SNAP-Ed to include multi-level and public-health approaches, which was operationalized through policy, systems, and environmental change strategies (PSE). This analysis examines how states incorporated and planned to use PSEs in SNAP-Ed program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Race and ethnicity are frequently regarded as reliable predictors of obesity where minority populations are considered to be especially vulnerable to higher rates of obesity [8,49,66,67]. The percentage of households receiving SNAP benefits (formerly known as food stamps) was included because there is vigorous debate as to whether the program increases or decreases obesity rates in low-income communities [49,[68][69][70][71]. Lastly, the percentage of the tract population with at least a bachelor's degree was included, as there is evidence that individuals with at least some college education are less likely to be obese [65,72,73].…”
Section: Datamentioning
confidence: 99%
“…Race and ethnicity are frequently regarded as reliable predictors of obesity where minority populations are considered to be especially vulnerable to higher rates of obesity [8,49,66,67]. The percentage of households receiving SNAP benefits (formerly known as food stamps) was included because there is vigorous debate as to whether the program increases or decreases obesity rates in low-income communities [49,[68][69][70][71]. Lastly, the percentage of the tract population with at least a bachelor's degree was included, as there is evidence that individuals with at least some college education are less likely to be obese [65,72,73].…”
Section: Datamentioning
confidence: 99%
“…In 2018, an estimated 26.8% of LAC households with incomes less than 300% of the federal poverty guidelines were food insecure, according to a population-based telephone questionnaire (30). While SNAP-Ed classes can help improve food security status (7,8), stress may contribute to worsening health behaviors despite participant knowledge about its negative health effects (31). Programs and interventions should work to integrate and maximize enrollment of eligible populations into nutrition assistance programs including SNAP, WIC, and senior meal programs.…”
Section: Implications For Public Healthmentioning
confidence: 99%
“…Examples of SNAP-Ed PSEs have included edible gardens in schools, incentive voucher programs in communities and health care settings, and healthy retail initiatives to promote FV consumption. Although states and implementing agencies have increasingly implemented PSEs throughout the past decade, limited research has characterized potential effects of SNAP-Ed programming at the community level ( 9 ). For example, 2 recent studies showed that for low-income caregivers of children who lived in high SNAP-Ed reach census tracts (versus low SNAP-Ed reach census tracts), PSEs were associated with increased FV consumption and decreased intake of sugar-sweetened beverages (SSBs) ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Race and ethnicity are frequently regarded as reliable predictors of obesity where minority populations are considered to be especially vulnerable to higher rates of obesity (Cockerham et al, 2017;Giuntella & Stella, 2017;Segal et al, 2017;Sohn et al, 2017). The percentage of households receiving SNAP benefits (formerly known as food stamps) was included because there is vigorous debate as to whether the program increases or decreases obesity rates in low-income communities (Meyerhoefer & Pylypchuk, 2008;DeBono, Ross, & Berrang-Ford, 2012;Gundersen, 2016;Segal et al, 2017;Burke et al, 2019). Lastly, the percentage of the tract population with at least a bachelor's degree was included, as there is evidence that individuals with at least some college education are less likely to be obese (Jackson et al, 2005;Ogden et al, 2010;Lawrence, 2017).…”
Section: Datamentioning
confidence: 99%